The Changing Amazon Hydrological Cycle—Inferences From Over 200 Years of Tree‐Ring Oxygen Isotope Data. Issue 10 (6th October 2022) - Baker, Jessica C. A.; Cintra, Bruno B. L.; Gloor, Manuel; Boom, Arnoud; Neill, David; Clerici, Santiago; Leng, Melanie J.; Helle, Gerhard; Brienen, Roel J. W.
Abstract: Changes to the Amazon hydrological cycle have important consequences for world's largest tropical forest, and the biodiversity it contains. However, a scarcity of long‐term climate data in the region makes it hard to contextualize recent observed changes in Amazon hydrology. Here, we explore to what extent tree‐ring oxygen isotope (δ 18 OTR ) chronologies can inform us about hydrological changes in the Amazon over the past two centuries. Two δ 18 OTR records from northern Bolivia and the Ecuadorian Andes are presented. The Ecuador record spans 1799–2012 ( n = 16 trees) and the Bolivia record spans 1860–2014 ( n = 32 trees), making them the longest δ 18 OTR records from the Amazon, and among the most highly‐replicated δ 18 OTR records from the tropics to date. The two chronologies correlate well at interannual and decadal timescales, despite coming from sites more than 1, 500 km apart. Both δ 18 OTR records are strongly related to interannual variation in Amazon River discharge measured at Óbidos, and accumulated upwind precipitation, suggesting a common climatic driver. In both records a strong increase in δ 18 OTR was observed up until approximately 1950, consistent with positive trends in the few other existing δ 18 O proxy records from across the Amazon. Considering all possible drivers of this long‐term increase, a reduction in rainout fraction over the basin driven by rising sea surface temperatures in the North Atlantic is suggested as the most likely cause. The upward trend in δ 18 OTR reverses over the past 1–2 decades, consistent with the observed strengthening of the Amazon hydrological cycle since approximately 1990. Plain Language Summary: Long‐term climate measurements from the Amazon are few and far between, so information about the climate in the past needs to come from alternative sources. This is essential to provide context for current climate variability such as the strengthening of the Amazon water cycle since the 1990s. One way we can reconstruct historical climate is using stable oxygen isotopes recorded in tree rings. Previous work has shown that tree‐ring oxygen isotopes from the western Amazon can tell you about the amount of rainfall over the entire basin. Here, we present tree‐ring isotope records from Ecuador and Bolivia that span the past two centuries, making them the longest tree‐ring oxygen isotope records from the region to date. We find that the two records are very similar to one another, despite coming from sites that are more than 1, 500 km apart, suggesting they are both influenced by the same climatic factors. We explore the climate signals that these records contain, including interpreting a long‐term positive trend in the isotope record until around 1950. We conclude that the most likely cause of this trend is a long‐term reduction in the fraction of incoming water vapor that falls as rainfall over the Amazon. Key Points: We present two well‐replicated tree‐ring oxygen isotope (δ 18 OTR ) records from tropical South America spanning the past two centuries These records capture important large‐scale climate signals, including interannual variation in Amazon basin‐wide precipitation A multi‐decadal long‐term increase in δ 18 OTR is interpreted as being primarily driven by a long‐term reduction in rainout fraction